2015
DOI: 10.1016/j.kjms.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy for large adrenal masses: Is it really more complicated?

Abstract: Laparoscopic treatment of large adrenal tumors is still questionable due to concern over the risk of malignancy as well as the technical difficulties. No exact dimensional cut-off has been described for laparoscopic adrenalectomy (LA). In this study, we reviewed our experience with LA for masses ≥ 8 cm and tried to determine the limitations of this surgery in this group of patients. Sixteen patients with adrenal mass ≥ 8 cm (Group 1) and 19 patients with adrenal mass < 8 cm (Group 2) treated with transabdomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
0
25
0
5
Order By: Relevance
“…The average operative time, estimated blood loss, perirenal drainage time, postoperative hospital stay, postoperative drainage, and transfusion rate were 176.3 ± 49.7 min, 247.2 ± 274.1 mL, 4.1 ± 1.02 days, 6.3 ± 1.4 days, 73.6 ± 47.9 mL, and 1/18, respectively. Compared with those in a previous study in which patients with large adrenal tumors (8 cm) underwent LTA, the operative time and hospitalization time were longer and the blood loss was greater, but complications such as conversion to OA and blood transfusion were reduced (Table ) . Moreover, Insang et al evaluated the surgical feasibility of RLA for tumors ≧5 cm and found that the operative time, estimated blood loss, postoperative hospital stay, transfusion, and surgical complications were 214.54 ± 76.04 min, 367.24 ± 275.11 mL, 9.26 ± 3.10 d, 6 (7.9%), and 13 (17.1%) respectively, for large adrenal tumors (7.10 ± 2.15 cm) (Table ) .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The average operative time, estimated blood loss, perirenal drainage time, postoperative hospital stay, postoperative drainage, and transfusion rate were 176.3 ± 49.7 min, 247.2 ± 274.1 mL, 4.1 ± 1.02 days, 6.3 ± 1.4 days, 73.6 ± 47.9 mL, and 1/18, respectively. Compared with those in a previous study in which patients with large adrenal tumors (8 cm) underwent LTA, the operative time and hospitalization time were longer and the blood loss was greater, but complications such as conversion to OA and blood transfusion were reduced (Table ) . Moreover, Insang et al evaluated the surgical feasibility of RLA for tumors ≧5 cm and found that the operative time, estimated blood loss, postoperative hospital stay, transfusion, and surgical complications were 214.54 ± 76.04 min, 367.24 ± 275.11 mL, 9.26 ± 3.10 d, 6 (7.9%), and 13 (17.1%) respectively, for large adrenal tumors (7.10 ± 2.15 cm) (Table ) .…”
Section: Discussionmentioning
confidence: 66%
“…First 6 cm and then 8 cm was regarded as the upper limit size for LA . Subsequently, another study suggested that laparoscopic transabdominal adrenalectomy (LTA) had similar effects on adrenal masses ≥8 cm and ≤8 cm in diameter and was a safe and feasible procedure for large lesions up to 15 cm . Furthermore, several studies comparing retroperitoneal laparoscopic adrenalectomy (RLA) and LTA have suggested that the RLA outcomes were superior to those of LTA, specifically the shorter surgery duration, reduced blood loss, lower postoperative pain, faster recovery, decreased length of hospital stay, improved cost‐effectiveness, and abolished risk of surgical access site herniation .…”
Section: Introductionmentioning
confidence: 99%
“…На сьогодні не зібрано достатнього обсягу репрезентативного клінічного матеріалу для формулювання універсальних показань і протипоказань до ендохірургії у цих категорій пацієнтів [7]. Наслідок цього -істотна різноманітність клінічних рекомендацій щодо лікування пацієнтів даної групи [8]. Активно дискутується максимальний розмір пухлини, що підлягає лапароскопічному видаленню.…”
Section: діагностично-лікувальний алгоритм комплексного хірургічного unclassified
“…A total of 9 studies 15-24 mentioned the comparison on LA and OA, and two studies 25,26 mentioned different diameter of adrenal tumor in LA. There exists controversy on the advantages of laparoscopy, as shown in the summarized information of related studies listed in Table 4.…”
Section: Studies On Laparoscopic Adrenalectomy Versus Open Proceduresmentioning
confidence: 99%